The influence of sex steroids on pineal enzymes - Daya, Santylal (Rhodes University, Faculty of Pharmacy, Pharmacy, 1982)
The influence of the gonadal sex steroids namely, estradiol, progesterone and testosterone on the two major enzymes responsible for the synthesis of melatonin in the pineal gland was investigated. These enzymes are Serotonin-N-acetyltransferase (SNAT) and Hydroxyindole-O-methyltransferase (Hl0MT). Testosterone was found to be the only sex steroid capable of influencing SNAT activity whereas all three of the sex steroids were found to influence Hl0MT activity in a biphasic dose-dependent manner. The influence of these sex steroids on radiolabeled serotonin metabolism by pineals in organ culture was also investigated. Ovariectomy, castration and the sex steroids were all found to alter the pattern of the radiolabeled serotonin metabolism by these pineal glands in organ culture.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Steroid hormones; Pineal gland; Testosterone; Progesterone